Odpowiedzi

2010-03-15T19:07:14+01:00
(2√3 + 2√2)³= (2√3+2√2)(2√3+2√2)(2√3+2√2)= 12*8(2√3+2√3)= 96(2√3+2√2)= 192√3+ 192√2
-5 ( 2x + 3 )( 3 - 2x ) - ( 5 - 2x ) ² = 5 ( 2x + 3 )( 3 - 2x ) - ( 5 - 2x )( 5 - 2x )= -5(6x-4x²+9-6x)-(25-10x-10x+4x²)= -30x+20x²-45+30x-25+10x+10x-4x²=16x²+20x-70
( 2√5 - 4 ) ³ = ( 2√5 - 4 )( 2√5 - 4 )( 2√5 - 4 ) =(20-8√5-8√5+16)(2√5-4) = (36-16√5)(2√5-4)= 72√5-144-160+64√5=136√5-304
( 3 + 3y)²-(4y -2)²-(3+y)(-y+3) = (3 + 3y)( 3 + 3y)- (4y -2)(4y -2)-(3+y)(-y+3)= 9+9y+9y+9y²-(16y²-8y-8y+4)-(-3y+9-y²+3y)=9+9y+9y+9y²-16y²+8y+8y-4+3y-9+y²-3y= -6y²+34y-4
-6y²+34y-4 --> y=2√3-2
-6y²+34y-4=-6( 2√3-2)(2√3-2)+34(2√3-2)-4= -6(12-4√3-4√3+4)+64√3-64-64= -72+24√3+24√3-24+64√3-64-4=112√3-164